2021
DOI: 10.1002/ldr.3875
|View full text |Cite
|
Sign up to set email alerts
|

Converting croplands to orchards changes soil microbial community composition and co‐occurrence patterns

Abstract: Soil microorganisms are key to uncovering the mechanisms driving variation in soil biogeochemical processes associated with land-use change. A large number of croplands have been converted to orchards on the Chinese Loess Plateau due to the increased economic benefits which result. However, the microbial community and their functional composition remain poorly understood. In this study, soil samples were collected from croplands and orchards. Soil physicochemical properties and the community (represented by 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 77 publications
0
11
1
Order By: Relevance
“…We demonstrated that the bacterial phyla Acidobacteria and Proteobacteria, fungal phyla Ascomycota and Basidiomycota, and protist phyla Cercozoa and Lobosa formed the most links with other microbial groups and are, therefore, potentially vital to soil food webs (Figure 4, Table S5), which indicated that these taxa are keystone and indicator taxa in the co‐occurrence patterns (Fournier et al, 2020; Wang, Wang, et al, 2021). Moreover, these taxa were the dominant groups in the microbial community, suggesting that a microbiome containing these taxa with a high abundance may have more links among groups than that with a low relative abundance.…”
Section: Discussionmentioning
confidence: 88%
“…We demonstrated that the bacterial phyla Acidobacteria and Proteobacteria, fungal phyla Ascomycota and Basidiomycota, and protist phyla Cercozoa and Lobosa formed the most links with other microbial groups and are, therefore, potentially vital to soil food webs (Figure 4, Table S5), which indicated that these taxa are keystone and indicator taxa in the co‐occurrence patterns (Fournier et al, 2020; Wang, Wang, et al, 2021). Moreover, these taxa were the dominant groups in the microbial community, suggesting that a microbiome containing these taxa with a high abundance may have more links among groups than that with a low relative abundance.…”
Section: Discussionmentioning
confidence: 88%
“…In view of their important functions in the soil carbon cycle (Chang et al, 2021; Yang et al, 2020), it was reasonable to believe that there were interactions among them. Nevertheless, a higher complex co‐occurrence network was found in farmland than in plantation/grassland, which resulted in higher community stability and interactions in farmland (Wang et al, 2021). The average path length was shorter in farmland than in plantation/grassland, which indicated that farmland might rapidly respond to variations of soil physicochemical factors through efficient pathways (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that most soil bacterial taxa may synergistically act or share similar ecological niches in the soil environment of teak plantations [ 72 ]. In addition, an increase in positive associations was observed with stand age, suggesting that the co-occurrence network between synergistic bacterial groups was enhanced [ 72 , 78 ]. We also found that the average path length (APL) value in the 45-y sites was the smallest, indicating that it was a small-world network [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the average path length (APL) value in the 45-y sites was the smallest, indicating that it was a small-world network [ 74 ]. The small-world network indicates that the bacterial community can respond quickly to changes in external environmental conditions [ 78 ]. Network analysis can not only be applied to determine how species occur together in niches but can also identify the keystone taxa that play a critical role in communities [ 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%